ANALYSIS OF THE POLITICAL MARKETING SUCCESS OF THE WINNING NATIONAL PARTY WITH LOCAL AFFILIATED PARTY IN ACEH - Wahyuddin Wahyuddin; Fuadi Fuadi; Falahuddin Falahuddin; Hanif Hanif (Faculty of Economics and Business, Universitas Malikussaleh, 2021)
The purpose of this study was to determine the level of success of the political marketing of the victory of the national party with its affiliated local party in Aceh. The political marketing concept of product, promotion, price and place is used in this study. Primary data was obtained by using a questionnaire. The research locations are two districts in the province of Aceh, namely Bireuen Regency and Pidie Jaya Regency, while sampling using Maximum Likelihood (ML) in the estimation model requires the use of a minimum sample size of 100. By setting the number of samples for each voter national parties and local party voters. The sample will be taken at convenience from each research location. The result of the study of the coefficient of determination (R2) is 0.269. This means that 26.9% changes in the dependent variable, namely the Decision to Choose a National Party, can be explained in the independent variables, namely Product, Promotion, Price, and Place. While the remaining 73.1% is explained by other variables outside the variables studied. This shows that the contribution of the independent variable has little impact on the dependent variable. While the results of the coefficient of determination of the Decision to Choose a Local Party is 0.672. This means that 67.2% changes in the dependent variable, namely the Decision to Choose a Local Party, can be explained in the independent variables, namely Product, Promotion, Price, and Place. While the remaining 32.8% is explained by other variables outside the variables studied. This shows that the contribution of the independent variable has an impact on the dependent variable.